Characterizing landscape patterns in urban-rural interfaces - Paola Ortiz-Báez; Pablo Cabrera-Barona; Jan Bogaert (Journal of Urban Management, 2021)
Due to new urbanization patterns, where cities' edges are becoming increasingly difficult to delimit, a better understanding of urban-rural gradients has become a key issue for urban planning. These interstitial territories are characterized for being highly heterogeneous, with hybrid and complex dynamics and -due to their landscape ambiguity and rapid transformation-frequently lack of clear regulations. Through calculation and analysis of landscape metrics in high resolution satellite images, this study proposes a novel and accurate method to identify urbanization patterns. It was applied to the urban-rural gradient of the Metropolitan District of Quito (MDQ), an Andean city. After analyzing five land use/land covers in six transects, results suggest that the MDQ presents patterns of urban diffusion and coalescence. The diffusion starts at the urban core and expand to rural parishes where some emerging traditional settlements merge, constituting a complex pattern of urbanization. Also, significant levels of fragmentation were identified for the vegetation cover in periurban areas, threatening the territory environmental sustainability. Finally, a multivariate cluster analysis was developed, evidencing five main tendencies of urbanization patterns. This knowledge can be particularly useful for urban planning in terms of reducing randomness in urban development processes. This paper proposes and tests an analytical approach which could be applied to other Latin-American cities, where urban expansion patterns remain unknown.
Keywords: 710; Landscape metrics; Landscape patterns; Multivariate clustering; Urban expansion; Urban-rural gradient